Bash Cookbook : Leverage Bash Scripting to Automate Daily Tasks and Improve Productivity. - Brash, Ron (Packt Publishing Ltd, 2018)
One of the most powerful tools that can be used almost every day is the Bash shell, but its true utility remains untapped by most users. Using a collection of recipes and intuitive lessons, the Bash Cookbook walks you through a series of exercises designed to teach you how to effectively use the Bash shell to create and execute your own scripts.